TNF‐α‐induced IL‐6 and MMP‐9 expression in immortalized ameloblastoma cell line established by hTERT. (21st November 2016) - Ohta, K; Naruse, T; Ishida, Y; Shigeishi, H; Nakagawa, T; Fukui, A; Nishi, H; Sasaki, K; Ogawa, I; Takechi, M
Abstract : Objective: Ameloblastoma (AM) shows locally invasive behaviour. However, biological investigations regarding regulation of gene expression associated with AM pathological features are difficult to perform, because AM cells can be passaged for a few generations due to senescence. We report a newly established immortalized AM cell line, AMB cells, by transfection with human telomerase reverse transcriptase (hTERT). Furthermore, we examined whether TNF‐ α modulates bone resorption‐related genes, IL‐6 and MMP‐9 in cooperation with TGF‐ β or IFN‐ γ . Materials and methods: Following transfection of an hTERT expression vector into AM cells using a non‐viral method, the effects of cytokines on the expressions of IL‐6 and MMP‐9 mRNA were examined using real‐time PCR. TNF‐ α ‐induced NF‐ κ B activity was examined by western blotting and transcription factor assays. Results: AMB cells continued to grow for more than 100 population doublings. Stimulation with TNF‐ α increased IL‐6 and MMP‐9 mRNA expressions, as well as NF‐ κ B activation. Furthermore, TGF‐ β and IFN‐ γ dramatically increased TNF‐ α ‐mediated expressions of MMP‐9 and IL‐6 mRNA, respectively, while those responses were suppressed by NF‐ κ B inhibitor. Conclusion: We established an immortalized AM cell line by hTERT transfection. TNF‐ α ‐mediated regulation of MMP‐9 and IL‐6 via NF‐ κ B may play an important role in the pathological behaviour of AMs, such as bone resorption.